A choline binding polypeptide of LytA inhibits the growth of Streptococcus pneumoniae by binding to choline in the cell wall. (November 2018) - Zhang, Zhikun; Zhang, Xinzhuo; Zhang, Luhua; Wang, Guangxi; Zeng, Jing; Zhang, Jinping; Hu, Xiaoyan; Zhou, Yingshun
Abstract Streptococcus pneumoniae is a pathogen that mainly affects children and elderly individuals. The numerous serotypes and increased resistance to antibiotics make the treatment of pneumococcal infections sometimes difficult. Asymptomatic colonization is the main reservoir forS. pneumoniae, but no vaccine or antibiotic treatment is effective in eliminating this reservoir. Here, we show that a simulated choline binding polypeptide (ChBp) of LytA has antimicrobial activity againstS. pneumoniae . ChBp showed specific antimicrobial activity against pneumococcal but not against non-streptococcal strains, and no cytotoxic effect was observed for 293t cell. The minimal inhibitory concentration (MIC) is between 10–25 μg/ml. In addition, we found ChBp functions by binding to the choline in the cell wall with a binding capacity between 3.25 and 7.5 × 10−6 g/CFU. The binding cannot kill, but can inhibit the growth of pneumococcal cells for up to 12 h (50 μg/ml). Viable cells were decreased by 50% at 18 h, and eliminated at 36 h of incubation. These results show that ChBp has potential for the treatment of pneumococcal disease, or for eliminating nasopharyngeal colonization.